Moral hypocrisy: Self-deception or impression management? - Gari Walkowitz; Jan-Erik Lönnqvist; Bernd Irlenbusch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In four studies (S1-S4; N = 320) we investigated whether moral hypocrisy (MH) is motivated by conscious impression management concerns or whether it is self-deceptive. In a dictator game, MH occurred both within participants (saying one thing, doing another; S1) and between participants (doing one thing when it is inconsequential, doing another thing when it affects payoffs; S2). People were willing to let an ostensibly fair coin determine payoffs only if they could fudge the results of the coin flip, suggesting that hypocrites do not deceive themselves (S3). Also supporting this view, MH was associated with adherence to Conformity values (S1-S2), indicative of a desire to appear moral in the eyes of others but not indicative of self-deception. Universalism values were predictive of moral integrity (S1, S3-S4). Applying our findings, we show that MH can be reduced by increasing the collective awareness about its prevalence in a specific situation (S4).
Keywords: A13; C91; M14; 330